Impact of integrated sustainability content into undergraduate business education. Issue 1 (2nd December 2019) - Hay, Rachel; Eagle, Lynne
Abstract : Purpose: This paper aims to compare the findings from a survey of a cohort of students at an Australian regional university across two time points: immediately on commencing their first semester of study and at the end of their final semester of study to determine whether, and in what ways, these students' views concerning sustainability appear to have changed. This paper reports on a longitudinal study of the attitudes, beliefs and perceptions of undergraduate business students regarding a range of sustainability issues. Design/methodology/approach: A paper-based questionnaire was delivered to approximately 250 first year and 150 third year students. Findings: A factor analysis shows small but statistically different positive differences, which indicate that the revised curriculum has been successful in raising student awareness and achieving behaviour change. Research limitations/implications: The study focussed on Australian undergraduate university business students, which reduced generalizability of the findings. Practical implications: The findings of this study can inform instructors in higher education of student attitudes towards sustainability and climate change adaption and in turn inform changes to tertiary curriculum in sustainability and climate change adaption. Originality/value: The authors confirm that the research is original and that all of the data provided in this paper is real and authentic. As the paper reports on the third phase of the longitudinal study, some parts of the methodology have been previously published but differ as they reflect the third phase of the study. The results of this study have not been previously published.